The Strange Case of Ermine de Reims : A Medieval Woman Between Demons and Saints - Blumenfeld-Kosinski, Renate, 1952- (Book collections on Project MUSE., 2015)
In 1384, a poor and illiterate peasant woman named Ermine moved to the city of Reims with her elderly husband. Her era was troubled by war, plague, and schism within the Catholic Church, and Ermine could easily have slipped unobserved through the cracks of history. After the loss of her husband, however, things took a remarkable but frightening turn. For the last ten months of her life, Ermine was tormented by nightly visions of angels and demons. In her nocturnal terrors, she was attacked by animals, beaten and kidnapped by devils in disguise, and exposed to carnal spectacles; on other nights, she was blessed by saints, even visited by the Virgin Mary. She confessed these strange occurrences to an Augustinian friar known as Jean le Graveur, who recorded them all in vivid detail. Was Ermine a saint in the making, an impostor, an incipient witch, or a madwoman? Renate Blumenfeld-Kosinski ponders answers to these questions in the historical and theological context of this troubled woman's experiences. With empathy and acuity, Blumenfeld-Kosinski examines Ermine's life in fourteenth-century Reims, her relationship with her confessor, her ascetic and devotional practices, and her reported encounters with heavenly and hellish beings. Supplemented by translated excerpts from Jean's account, The Strange Case of Ermine de Reims brings to life an episode that helped precipitate one of the major clerical controversies of late medieval Europe, revealing surprising truths about the era's conceptions of piety and possession.